Determination of Pavement Surface Regularity through the Calculation of the International Roughness Index (IRI) - Badilla Vargas, Gustavo (2025)
The International Roughness Index (IRI) has been a widely used parameter in order to determine the pavement surface characteristics in roads. Recently, in Costa Rica, the Administration has been introducing the measurement of IRI as a parameter of acceptance of several road construction works. However, it has not been possible to achieve an appropriate implementation of this index. The article presents the main details, cares, and procedures involved in the calculation of the IRI, with the purpose of being considered in the definition of specifications to accept projects or in the evaluation of the road network.